The Effect of NPK and Guano Fertilizer on the Growth and Yield of Bogor Peanut Plants (Vigna subterranea (L.) Verdc.) - Vanessa Gabrielle Liemendy; Widiwurjani Widiwurjani; Juli Santoso (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
This study aimedto evaluate the effects of combined NPK fertilizer and guano application on the growth and yield of Bambara groundnut (Vigna subterranea (L.) Verdc.). The experiment employed a factorial randomized block design with two factors: NPK fertilizer dosage (25%, 50%, 75%, and 100% of recommended rates) and guano dosage (5, 10, and 15 tons/ha). Observed parameters included plant height, leaf count, number of flowers, number of pegs, and fresh/dry pod weight per plant. Results demonstrated that the combination of 25% NPK and 15 tons/ha guano significantly improved plant height (43.29 cm), flower count (47.33), and fresh pod weight (81.73 g/plant). Guano alone also exhibited a substantial effect on both vegetative and generative growth, with the highest results observed at 15 tons/ha. The combination of low NPK and high guano dosages enhances Bambara groundnut productivity sustainably.